Incidence of reproductive prolapse in cows in western Thailand: Severity and treatment - Srisomrun, Smit; Arunvipas, Pipat; Ratanapob, Niorn; Sangmalee, Anawat (Agriculture and Natural Resources, 2024)
Importance of the work: There is limited information on reproductive prolapse in Thai cattle, especially in terms of characteristics of the demographic and severity. Objectives: To determine the demographic characteristics and severity of reproductive prolapses of cattle in western Thailand. Also, to evaluate the associated factors and the response to a treatment. Materials and Methods: From January 2016 to June 2020, data were collected from 100 reproductive prolapse cases submitted to Kasetsart University Veterinary Teaching Hospital Kamphaeng Saen. The obtained data included grade and part of the prolapsed organ, type of cattle, parity, time and the history of the previous prolapse and the exercise allowance. Statistical analysis was performed to identify the severity and factors associated with the severity of reproductive prolapse using Fisher's exact test and logistic regression. Results: A total of 100 reproductive prolapse cases were classified as 8 intermittent vaginal prolapse, 15 continuous vaginal prolapse, 56 cervical prolapse and 21 uterine prolapse. Beef cattle were the dominant cases over dairy cattle (79 and 21 cases, respectively). The factor associated with the severity found in this study was the type of cattle, with greater severity found in dairy compared to beef cattle with the odds ratio of 10.37 (95% CI 3.42, 31.42; p < 0.001). Main finding: Most cases of reproductive prolapse found in this study were vaginal and cervical prolapse. Almost 80 % of the cases were beef cattle. Meanwhile, the proportion of uterine prolapse was greater in dairy cattle than in beef cattle.